Pengaruh Penggunaan Audiovisual dalam Meningkatkan Keterampilan Istima’ - Dillah Nur Syafanah; Novalia Safithri; Roudotul Jannah; Wahyu Hidayat; Dina Indriana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the impact of using audiovisual media on improving the Arabic listening skills (maharatul istima') of class X students at MA Al- Maghfiroh. The method used was an experiment with a pretest-posttest control group design. The research sample consisted of two groups, namely the experimental class which used audiovisual media in the form of animated videos and the control class which used regular audio media. The research instrument has been tested for validity and reliability, with 18 of the 20 instrument items declared valid and a Cronbach's Alpha value of 0.823. Data were analyzed through normality tests, homogeneity tests, t-tests, and N-Gain calculations. The results showed that the average posttest score for the experimental class (81.20) was higher than the control class (70.50). The N-Gain value for the experimental class is 0.55 (medium category), while for the control class it is 0.38 (medium category). The t-test shows that there is a significant difference between the two groups, with the calculated t value (2.410) greater than the t table (2.080) and a significance of 0.020. These findings indicate that the use of audiovisual media, especially animated videos, is significantly more effective in improving students' listening skills compared to regular audio media. These results recommend the application of audiovisual media in Arabic language learning to support the improvement of istima skills.